An efficient nanostructured copper(I) sulfide-based hydrogen evolution electrocatalyst at neutral pH. (10th October 2016) - Fan, Meihong; Gao, Ruiqin; Zou, Yong-Cun; Wang, Dejun; Bai, Ni; Li, Guo-Dong; Zou, Xiaoxin
Abstract: Developing efficient nonprecious electrocatalysts to accelerate the hydrogen evolution reaction (HER) is of importance for the hydrogen energy technology. Herein, we report the in situ growth of single-crystalline γ -Cu2 S nanoplates on copper foam (CF) in a hydrothermal system, with the assistance of a small amount of cobalt(II) acetate. The presence of cobalt(II) acetate in the synthesis system has been proven to have multiple roles: (i) inhibiting the formation of copper(I) oxide (Cu2 O); (ii) directing the fromation of the crystal phase of γ - Cu2 S; and (iii) controlling the morphology of the as-formed γ - Cu2 S. Furthermore, we show that the resulting γ - Cu2 S/CF material can serve as an efficient integrated 3D electrode toward HER at neutral pH. The γ - Cu2 S/CF delivers a current density of 10 mA/cm 2 at a small overpotential of 190 mV, gives 100% Faradaic yield during HER, and maintains its electrocatalytic activity for >10 hours. To the best of our knowledge, this is the first time that a copper(I) sulfide-based material is demonstrated to electrocatalyze the HER efficiently. Identifying copper(I) sulfide as the active phase for HER and constructing advantageous 3D γ -Cu2 S nanostructure via an ion-induced method might open a door for the further investigation of Cu-based hydrogen-evolution electrocatalysts.